南北极海区碳循环与全球变化研究 - 高众勇; 陈立奇; 王伟强 (2002)
南北极是全球变化研究领域中十分重要的地区 ,也是世界大洋对全球变化反馈的一个重要窗口。文章论述了南北极海区碳循环研究的国内外研究动态 ,阐述了目前南大洋及北冰洋的生产力水平及碳收支平衡状态 ,讨论需要进一步研究的一些存在问题以及将来的发展方向。目前的研究表明 ,北极的生产力比历史上所认为的要高 ,在全球变化的作用下 ,其将成为越来越重要的碳汇区 ;南大洋主控着人为源CO2 的海气交换通量 ,而生产力所受到的限制也影响着其吸收CO2 的潜力。目前制约着对两极碳循环进一步认识所缺乏的资料包括 :极区碳汇的时空变异、南大洋的Fe限制及Fe假说、紫外增强对极区碳循环可能产生的影响等。今后研究的重点将集中在全球变化对两极碳循环的影响及其反馈 ,碳循环的机制及其动力学过程 ,以及通过碳循环人为干预全球变化的可行性。近年来 ,中国也十分重视极区碳循环的研究 ,取得了许多积极的成果。我们的研究结果表明 ,在 80°E～ 80°W之间 ,南大洋基本上是大气CO2 的汇 ,其中在 45°W～ 30°W及 10°W～ 10°E之间 ,是CO2 的强汇区。北冰洋的一些海区也表现为很强的碳汇区。计算得出 ,楚科奇海及其附近海区 7月到 9月CO2 吸收通量为 0 13g/ (m2 ·d) (碳 )。南大洋夏季CO2 吸收通量为 0 1g/ (m2 · The polar oceans are very significant areas in the study of global change especially for carbon cycling. This paper dissertates the developments of carbon cycling in the sea area of both poles, expatiates the level of their primary production and carbon balance, and discusses the existing problem and the trends in the future. Present study has shown that the Arctic Ocean is an area with high production, and it will become a more important sink of carbon under the future's global climate change, the Southern Ocean is also a significant carbon sink, and it is affected from the limitations of production to its further uptake of CO 2 . Some difficulties to profoundly understand carbon cycle in the polar regions include the spatio\|temporal difference of the carbon sink in the polar, iron hypothesis, and the effect of increasing ultraviolet ray on the carbon cycle in the polar. Future's work will stress on the effect of global change on the carbon cycling and its feedback, the mechanism of carbon cycling in the polar ocean, and its dynamic process, and the feasibility of intervention to the global warming. Chinese polar research has made rapid progress in this area. Our research in those areas shows that the Southern Ocean and the Arctic Ocean would play a most important role in absorbing anthropogenic carbon dioxide. The results show that there is a sink for atmospheric CO 2 during summer between 80°W to 80°E in the Southern Ocean, an average of 0.1 g C/(m 2 ·d) for total CO 2 fluxes. Chucki Sea in the Arctic Ocean also appears as a carbon sink with 0 13 g C/(m 2 ·d) for total CO 2 fluxes. 国家重点自然科学基金资助项目 ( 4 9836 0 0 1) ;; 中国首 次北极科学考察资助项目